The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1089/hum.2010.194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adeno-Associated Viral Vectors for Liver-Directed Gene Transfer in Dogs

Abstract: This study evaluated six adeno-associated viral (AAV) vectors expressing green fluorescent protein (GFP) from the liver-specific thyroid hormone-binding globulin (TBG) promoter made with novel capsids in canine liverdirected gene transfer. Studies in 1.5-month-old dogs, which were administered vector through a peripheral vein, showed that AAV8 capsid vectors had the most favorable performance profiles. Interestingly, the absolute levels of hepatocyte transduction achieved with AAV8 were lower in dogs compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 55 publications
6
39
0
Order By: Relevance
“…The scAAV8-TBG-dnMSTAT construct was designed to express the secreted canine myostatin Belgian Blue inhibitory peptide (Kambadur et al, 1997) containing a D76A mutation that confers protease resistance (Wolfman et al, 2003) under control of the liver-specific thryroid-hormone binding globulin (TBG) promoter (Bell et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scAAV8-TBG-dnMSTAT construct was designed to express the secreted canine myostatin Belgian Blue inhibitory peptide (Kambadur et al, 1997) containing a D76A mutation that confers protease resistance (Wolfman et al, 2003) under control of the liver-specific thryroid-hormone binding globulin (TBG) promoter (Bell et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The scAAV8-TBG-dnMSTAT vector was tested in two normal canines prior to its use in GRMD canines. One normal canine received 10 12 genome copies (gc)/kg vector via hepatic artery infusion as previously described (Bell et al, 2011), and one normal canine received 10 12 gc/kg vector via peripheral intravenous (IV) infusion (cephalic vein). The remaining dogs used in the study were GRMD canines, which received either 1.7 · 10 12 gc/kg vector (n = 4) via IV infusion or no treatment (n = 3).…”
Section: Animal Use and Vector Delivery Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent immune evasion of AAV8 to antigenic transgene products in mouse models is not relevant to larger animals such as primates and dogs (23)(24)(25), in which vibrant and destructive CTLs are elicited. In fact, the study of AAVrh32.33 in mice may better reflect the anticipated biology of other AAV capsids in large animals and humans.…”
Section: Figurementioning
confidence: 99%
“…However, such high levels of hepatic cell transduction by AAV8-based vectors observed in mice have yet to be repeated in larger animal models. Levels of gene transfer similar to those found in mice have been demonstrated in studies of infant rhesus macaques (73), and recent data suggest lower efficiency in dog models (7). Despite these results, studies in dogs with hemophilia have demonstrated AAV8-mediated continuous expression of canine factor VIIa at levels above normal values (46).…”
mentioning
confidence: 92%